Taxonomic notes on Trigonidium and related groups with one new species from the Philippines (Orthoptera: Trigonidiidae; Trigonidiinae) - Tan, Ming Kai; Baroga-Barbecho, Jessica B.; Yap, Sheryl A. (Zootaxa, 2019)
The taxonomy of Old World Trigonidiinae (sword-tailed crickets) is in need of major revision. This includes its type genus Trigonidium. Various authors have different opinions on what constitutes the subgenera and species of Trigonidium s. l. and this has led to considerable confusion and inconsistencies. Recent use of molecular data has helped make some progress in resolving some of these problems, but there are still limitations. In this paper, we aim to provide a baseline to resolve the confusion in the taxonomy of Trigonidium s. l. Firstly, we provide a literature review of the contentious taxa related to Trigonidium and also provide some recommendations on future work for Trigonidium s. l. Secondly, we reanalysed the gene tree (sensu Lu et al., 2018) using more DNA sequences from GenBank to test whether Trigonidium s. str. and Paratrigonidium should be considered separate genera or subgenera of Trigonidium s. l. However, the gene tree based on current data was not conclusive. Lastly, we describe a new species of Trigonidium s. str. from Siargao Island, Mindanao (Philippines): Trigonidium solis sp. nov.